2003
DOI: 10.1038/nm969
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of breast cancer by chemical modulation of vulnerable zinc fingers in estrogen receptor

Abstract: Current antiestrogen therapy for breast cancer is limited by the mixed estrogenic and antiestrogenic activity of selective estrogen receptor modulators. Here we show that the function of zinc fingers in the estrogen receptor DNA-binding domain (DBD) is susceptible to chemical inhibition by electrophilic disulfide benzamide and benzisothiazolone derivatives, which selectively block binding of the estrogen receptor to its responsive element and subsequent transcription. These compounds also significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 37 publications
4
84
0
Order By: Relevance
“…Studies have shown that prevention of ER binding to ERE sequences of responsive genes by exogenously introduced ERE decoys (21) or electrophilic agents that disrupt zinc-fingers of ERα (22)(23)(24) represses E2-mediated growth of ERpositive breast cancer cells. Complementing this, we recently reported that genomic responses from the ERE-dependent pathway mediated by E2-ER are required to suppress the growth of ER-negative cells as well (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that prevention of ER binding to ERE sequences of responsive genes by exogenously introduced ERE decoys (21) or electrophilic agents that disrupt zinc-fingers of ERα (22)(23)(24) represses E2-mediated growth of ERpositive breast cancer cells. Complementing this, we recently reported that genomic responses from the ERE-dependent pathway mediated by E2-ER are required to suppress the growth of ER-negative cells as well (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In medicine, benzisothiazole derivatives act as antibiotic agents, 3 as phospholipase inhibitors in the treatment of hepatic diseases, 4 as inhibitors of the human leukocyte elastase, 5,6 and as selective blockers of the estrogen receptor, in the treatment of breast cancer. 7 A new class of substituted benzisothiazolones has shown antiviral activity against retroviruses (e.g., HIV virus), 8 and the first nonbenzoannelated 4-amino-2,3-dihydroisothiazole 1,1-dioxide, lacking a 3-oxo group, has recently been described and shows anti-HIV-1 activity. 9,10 Pseudosaccharyl ethers have particularly important synthetic uses as intermediate compounds for reductive cleavage of the C-O bond in phenols and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has also been shown that some benzisothiazolone derivatives selectively block binding of the estrogen receptor in breast cancer. Therefore, these compounds are being currently used in antiestrogen therapy for breast cancer [9]. More recently, a new class of substituted 2-benzisothiazolones has been proven to exhibit antiviral activity against retroviruses (e.g., HIV virus) [10].…”
Section: Introductionmentioning
confidence: 99%